Identifying the Components of the E-Government Governance Model with an Approach to Creating and Developing Digital Businesses - Chabok, Fereshteh; Dadashkarimi, Yahya; Nejad Hajali Irani, Farhad (Digital Transformation and Administration Innovation, 2025)
This study aims to identify and categorize the key components of an e-government governance model that facilitates the creation and development of digital businesses in Iran. The research employed a qualitative methodology using semi-structured interviews with 13 purposively selected experts, including senior managers, policymakers, scholars, and digital entrepreneurs. Participants were chosen based on their expertise and active engagement in the fields of e-government and digital business. Data collection was conducted through recorded face-to-face interviews, each lasting between 45 to 70 minutes. The interview protocol included open-ended questions focusing on governance mechanisms, infrastructure, regulatory frameworks, and cross-sector collaboration. Thematic analysis was applied to analyze the transcribed interviews. Initial coding resulted in 238 raw codes, which were refined into 57 basic themes. These were further categorized into 15 organizing themes and synthesized into 7 overarching (global) themes. The analysis revealed that effective e-government governance for digital business development relies on seven global themes: smart policy-making and digital management, technological infrastructure and interoperability, integrated digital services and collaborative platforms, human resource empowerment and innovative culture, supportive legal frameworks, stakeholder collaboration, and continuous evaluation mechanisms. These themes reflect the interdependence of institutional, legal, technical, and participatory factors. Furthermore, the findings emphasize the necessity of coordinated policymaking, user-centered platforms, data security, inter-organizational collaboration, and adaptive evaluation processes to sustain digital transformation and entrepreneurial growth. The study concludes that a robust and multidimensional e-government governance model must integrate strategic policymaking, institutional agility, stakeholder participation, and technological inclusivity to foster digital entrepreneurship. The proposed framework offers actionable insights for policymakers seeking to harmonize public sector digitalization with private sector innovation and economic development.